US Inflation Dynamics 1981-2007: 13,193 Quarterly Observations - Gregor W. Smith (Queen's University, Department of Economics, 2008)
The new Keynesian Phillips curve (NKPC) restricts multivariate forecasts. I estimate and test it entirely within a panel of professional forecasts, thus using the time-series, cross-forecaster, and cross-horizon dimensions of the panel. Estimation uses 13,193 observations on quarterly US inflation forecasts since 1981. The main finding is a significantly larger weight on expected future inflation than on past inflation, a finding which also is estimated with much more precision than in the standard approach. Inflation dynamics also are stable over time, with no decline in inflation inertia from the 1980s to the 2000s. But, as in historical data, identifying the output gap is difficult.
Keywords: E31; E37; C23; 330; forecast survey; new Keynesian Phillips curve; Inflation; Wirtschaftsprognose; Phillips-Kurve; USA